An Ecocritical Analysis of Young Adult Dystopian Novel in Veronica Rossi's Under The Never Sky (Universitas Islam Negeri Sunan Ampel Surabaya, 2017)
This study aims to describe the representation of nature and the interaction of Aria and Peregrine as main characters with nature. Descriptive qualitative method is used by applying Garrad's theory of ecocriticism and Basu's perspective on dystopian literature. The results of this study are: first, pastoral is represented by the distiction of the town and country. In the novel town is reprsented as Reverie and country as Death Shop. Second, Wilderness is represented by the wilderness of society in the Reverie and Death Shop and the wilderness of Death Shop's land. Third, Apocalypse is represented by the portrayal of foreboding doom and human eradication in the novel. The setting of place and time is the result of natural disaster and the development of technology takes control in human's life. The interaction of Aria and Peregrine shows human coexist with nature, human takes experience, learns knowledge and makes relation with nature.